2022
DOI: 10.1097/md.0000000000030710
|View full text |Cite
|
Sign up to set email alerts
|

Anti-aging protein klotho was associated with vitamin B12 concentration in adults

Abstract: Previous studies have reported that serum klotho and vitamin B12 levels are valuable aging-related markers. However, studies supporting the association between serum klotho and vitamin B12 levels are lacking. We investigated the association between serum klotho and vitamin B12 concentrations in adults in the United States. The analytic study sample was 2065 aged 40 to 79 who participated in the 2011 to 2014 National Health and Nutrition Examination Survey (NHANES). Serum klotho and vitamin B12 collected from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Besides, in an observational case-control study that included 40 thalassaemia patients and 41 healthy controls, there was no correlation between iFGF23 and Klotho concentrations and serum ferritin levels after controlling for age or BMI [ 18 ]. Interestingly, a current analysis of data obtained from the NHANES study found that increased serum Klotho concentrations were significantly associated with higher vitamin B12 concentrations [ 19 ]. Klotho may also increase the risk of anemia by affecting the reduction of anemia-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, in an observational case-control study that included 40 thalassaemia patients and 41 healthy controls, there was no correlation between iFGF23 and Klotho concentrations and serum ferritin levels after controlling for age or BMI [ 18 ]. Interestingly, a current analysis of data obtained from the NHANES study found that increased serum Klotho concentrations were significantly associated with higher vitamin B12 concentrations [ 19 ]. Klotho may also increase the risk of anemia by affecting the reduction of anemia-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of functions can be performed by S-Klotho, like a hormone in cells and tissues that do not express Klotho, including inhibition of oxidative stress and inflammation [23]. ELISA-measured levels of S-Klotho have been established as a straightforward and significant marker of aging [24], thus finding widespread usage in population-based studies to investigate factors influencing aging-related diseases and their associations [16,25,26]. For this study, we sought to complement existing epidemiological research on the relationship between dietary vitamin C consumption and serum Klotho concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced bioavailability of vitamin B12 and folic acid metabolism impairment have also been demonstrated in aging [24][25][26] and supplementation with folates and B12 has been demonstrated to possess anti-aging effects in experimental models [27][28][29]. Other proposed treatments for treating aging-associated manifestations include metformin, stem cells and hyaluronic acid (either injected or topically applied), as well as other cosmetic and aesthetic procedures [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%